The Bielski brothers : the true story of three men who defied the Nazis, saved 1.200 Jews, and built a village in the forest - Duffy, Peter (HarperCollins, 2003)
"In 1941, three young men--brothers, sons of a miller--witnessed their parents and two other siblings being led away to their eventual murders. It was a grim scene that would, of course, be repeated endlessly throughout the war. What makes this particular story of interest is how the survivors responded. Instead of running or capitulating or giving in to despair, these brothers--Tuvia, Zus, and Asael Bielski--did something else entirely. They fought back, waging a guerilla war of wits and cunning against both the Nazis and the pro-Nazi sympathizers. Along the way they saved well over a thousand Jewish lives"--Book jacket.